The Influence of Communication and Teamwork on Employee Performance at PT. Aneka Warna Indah in Jakarta - Armadhan, Rizky Tinto; Joesyiana, Kiki; Mar’aini, Mar’aini (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
The purpose of this study was to determine the effect of communication and teamwork on employee performance at PT Aneka Warna Indah in Jakarta. The place of this research was carried out at PT Aneka Warna Indah in Jakarta. This research is a quantitative study with communication and teamwork variables on employee performance. This study uses data collection techniques by distributing questionnaires. The number of samples in this study were 40 respondents who were taken using a purposive sampling technique. The data analysis technique used is multiple linear regression, coefficient of determination and hypothesis testing. Based on the results of the study, the results of multiple linear regression analysis yielded a value of -27.974 + 0.510X1 + 0.833X2 and the results of the communication t test (X1) used the t test with t count = 3.453 > t table = 2.02619 teamwork (X2) yielded t count = 2.385 < t table = 2.02619. F test results Fcount > Ftable or 56,747 > 3.25 with a significant value of 0.000 < 0.05 and the results of the coefficient of determination test yield Adjusted R Square = 0.746, meaning 74.6% simultaneously the communication variable (X1) and teamwork (X2) ) contributed 74.6% to teamwork (Y) at PT Aneka Warna Indah in Jakarta, while the remaining 25.4% was contributed by other variables not examined in this study.